2015
DOI: 10.1037/neu0000195
|View full text |Cite
|
Sign up to set email alerts
|

The imagination inflation effect in healthy older adults and patients with mild Alzheimer’s disease.

Abstract: Objective The imagination inflation effect is a type of memory distortion defined as an increased tendency to falsely remember that an item has been seen, or an action has been performed, when it has only been imagined. For patients with very mild Alzheimer’s disease (AD), susceptibility to the imagination inflation effect could have significant functional consequences in daily life. Method We assessed whether patients with very mild AD were more or less susceptible to the imagination inflation effect when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(44 citation statements)
references
References 64 publications
1
40
3
Order By: Relevance
“…These studies, in general, have demonstrated that patients with AD have a higher rate of false memory, especially when gist-information is strengthened (e.g., Balota et al, 1999; Budson, Daffner, Desikan, & Schacter, 2000; Budson, Desikan, Daffner, & Schacter, 2001; Budson, Sullivan, Daffner, & Schacter, 2003; O'Connor et al, 2015; Gallo et al, 2006). Memory test lists used in these studies are often composed of an unequal number of items, usually split into a third of old items, a third of unstudied critical lure items, and a third of unrelated new items.…”
Section: Discussionmentioning
confidence: 99%
“…These studies, in general, have demonstrated that patients with AD have a higher rate of false memory, especially when gist-information is strengthened (e.g., Balota et al, 1999; Budson, Daffner, Desikan, & Schacter, 2000; Budson, Desikan, Daffner, & Schacter, 2001; Budson, Sullivan, Daffner, & Schacter, 2003; O'Connor et al, 2015; Gallo et al, 2006). Memory test lists used in these studies are often composed of an unequal number of items, usually split into a third of old items, a third of unstudied critical lure items, and a third of unrelated new items.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MCI and mild AD dementia show impairments in recognizing and recalling information compared to healthy older adults (Budson et al, 2004; Budson, Wolk, Chong, & Waring, 2006; Budson et al, 2007; Dalla Barba, Nedjam, & Dubois, 1999; Embree, Budson, & Ally, 2012). Additionally, these patients show increased rates of false memories (Balota et al, 1999; Budson, Daffner, Desikan, & Schacter, 2000; Gallo et al, 2006; Hildebrandt, Haldenwanger, & Eling, 2009; O’Connor et al, 2015), which can create stressful and frustrating situations for patients and caregivers, as well as limiting a patient’s ability to live independently. False memories are often due to failures in monitoring the source of the information.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with Alzheimer’s disease (AD) dementia have been shown to exhibit higher rates of false recognition and recall relative to healthy age matched peers (Balota et al, 1999; Budson et al, 2000; Gallo et al, 2006; O’Connor et al, 2015). In false memory studies utilizing study lists of semantically related items (e.g., door, glass, pane, shade , etc.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this result, we have shown that elaborative processing can be detrimental to memory in these patients. In O’Connor et al (2015), participants were asked to perform, imagine, or listen to actions. Later, they re-imagined performing all actions 0, 1, or 3 times (regardless if they performed it, imagined it, or listened to it initially).…”
Section: Discussionmentioning
confidence: 99%
“…Healthy older adults have been shown to rely more on gist for their memory judgments (Gallo, Bell, Beier, & Schacter, 2006; Koutstaal & Schacter, 1997; Norman & Schacter, 1997). In comparison to healthy older individuals, patients with AD dementia exhibit more false memories and memory distortions (Balota et al, 1999; Budson, Daffner, Desikan, & Schacter, 2000; Budson, Sitarski, Daffner, & Schacter, 2002; Budson, Todman, Chong, et al, 2006; Budson, Todman, & Schacter, 2006; Budson et al, 2003; O’Connor et al, 2015). Patients with AD dementia have been shown to have higher rates of false memory to critical lures when matched on true memory performance (Balota et al, 1999).…”
Section: Introductionmentioning
confidence: 98%